Analysis of Schwann Cell Migration and Axon Regeneration Following Nerve Injury in the Sciatic Nerve Bridge - Chen, Bing; Chen, Quan; Parkinson, David B.; Dun, Xin-peng (Frontiers in Molecular Neuroscience, 2019)
While it is proposed that interaction between Schwann cells and axons is key for successful nerve regeneration, the behaviour of Schwann cells migrating into a nerve gap following a transection injury and how migrating Schwann cells interact with regenerating axons within the nerve bridge has not been studied in detail. In this study, we combine the use of our whole mount sciatic nerve staining with the use of a PLP-GFP mouse model to mark Schwann cells and have examined the behaviour of migrating Schwann cells and regenerating axons in the sciatic nerve gap following a nerve transection injury. We show here that Schwann cell migration from both nerve stumps starts later than the regrowth of axons from the proximal nerve stump. The first migrating Schwann cells are only observed 4 days following mouse sciatic nerve transection injury. Schwann cells migrating from the proximal nerve stump overtake regenerating axons on day 5 and form Schwann cell cords within the nerve bridge by 7 days post-transection injury. Regenerating axons begin to attach to migrating Schwann cells on day 6 and then follow their trajectory navigating across the nerve gap. We also observe that Schwann cell cords in the nerve bridge are not wide enough to guide all the regenerating axons across the nerve bridge, resulting in regenerating axons growing along the outside of both proximal and distal nerve stumps. From this analysis, we demonstrate that Schwann cells play a crucial role in controlling the directionality and speed of axon regeneration across the nerve gap. We also demonstrate that the use of the PLP-GFP mouse model labelling Schwann cells together with the whole sciatic nerve axon staining technique is a useful research model to study the process of peripheral nerve regeneration.